Finite nonabelian 2-groups all of whose minimal nonabelian subgroups are isomorphic to M2n+1 - Janko, Zvonimir (Ischia Group Theory 2010, 2012)
We give a complete classification of the title groups which generalizes a special case for n = 3.
Im Titel ist "2n+1" tiefgestellt
Gesehen am 23.02.2018
Keywords: Konferenzschrift